Exploring the experience of meaning-centered group psychotherapy among Chinese cancer patients during active treatment: a descriptive qualitative study - Wang, Shuman; Zheng, Mimi; Zhu, Yu; Zhang, Lijuan; Li, Xiaoru; Wan, Hongwei (Frontiers in Psychiatry, 2023)
Meaninglessness poses a significant psychological challenge for cancer patients, negatively affecting their quality of life and increasing the risk of suicide. Meaning-Centered Group Therapy (MCGP) is an intervention designed specifically to enhance the meaning of life of cancer patients. Extensive research has documented its effectiveness across various cultures and populations. However, limited research has been conducted on the subjective experiences and perspectives of participants engaged in MCGP. Thus, the purpose of this study was to employ a qualitative design to explore the experiences and viewpoints of Chinese cancer patients who have undergone MCGP.Within a two-week timeframe following the conclusion of MCGP, semi-structured interviews were administered to twenty-one participants who had engaged in the therapy. The interview data were transcribed and subjected to thematic analysis.Four main themes were identified: (a) Self-perceived personal change, (b) Overall experience of group therapy, (c) Barriers to participation of MCGP, and (d) Suggestions for future interventions.Despite the barriers to participation in the MCGP process, the overall experience for Chinese cancer patients undergoing active treatment is valuable and positive, providing multiple benefits. Future studies could explore the adaptation of MCGP to a broader range of cancer populations and diverse study populations.